Highly selective derivative spectrophotometric determination of tin (II) in alloy samples in the presence of cetylpyridinium chloride - Varghese, Anitha (Acta chimica slovenica, 2006)
A simple, selective and sensitive spectrophotometric method has been developed for the determination of tin(II) using a newly synthesised reagent diacetylmonoxime p-hydroxybenzoylhydrazone in cationic micellar medium. The molar absorptivity and Sandell's sensitivity of the coloured species are 3.20*104 L mol-1 cm-1 and 3.6 ng cm-2 respectively. Beer's law is obeyed between 0.25-2.76 g mL-1 of Sn(II)) at 430 nm. The stoichiometry of the complex was found to be 1Č2 (metal: ligand). A highly selective first order derivative spectrophotometric method for the determination of tin is also reported. The developed procedure has been successfully applied for the determination of tin in various alloy samples and synthetic mixtures of some low melting alloys.
Keywords: analizna kemija; kemijska analiza; kositer; površinsko aktivne snovi; spektralna analiza; spektrofotometrija; zlitine